As potencialidades do ensino de entomologia através do uso de metodologias ativas no ensino fundamental - Wommer, Fernanda Gabriela Bitencourt (2021)
This doctoral thesis investigates whether the use of Active Methodologies can promote the deepening of important scientific concepts in middle school through, the entomology theme. This study is presented in the form of three articles and a manuscript that seek, through a logical sequence, to present the results obtained in the studies carried out. Article 1 proposes a classification and categorization of Active Learning Methodologies, in article 2 we present the gamified activity Insects GO that was developed in an middle school, where students had to actively engage in tasks that involved scientific concepts about the entomology. In manuscript 1, we investigated the importance of inserting the History of Science as a strengthening of learning in middle school, and the last article presents the experience reporting a didactic activity carried out through non-face-to-face activities in 2020 and had as main objective engage students in the design and construction of an insect hotel, developing skills and presenting concepts relevant to the study of middle school science. This study presents a new perspective of learning about scientific concepts through the use of Active Methodologies involving the entomology theme, for this, quantitative and qualitative aspects capable of determining the involvement, motivation and learning of the students involved were analyzed.